First record of invasive Stenochrus portoricensis Chamberlin, 1922 (Arachnida: Schizomida: Hubbardiidae) from the Southern region of Brazil - Fabio Akashi Hernandes; James Craig Cokendolpher; Luiz Carlos Pinho (Papéis Avulsos de Zoologia, 2024)
Abstract Herein we report for the first time a schizomid for the Southern region of Brazil, Stenochrus portoricensis Chamberlin, 1922 (Schizomida: Hubbardiidae), found in association with termite nests. This is the southernmost record of any schizomid for the Neotropical region. We hypothesize that the species was recently introduced by the sudden population growth of Florianópolis - along with the intense touristic activity - which might have contributed to the inadvertent transportation of this species.